PENGARUH WAKTU AUSTENITISASI PADA PROSES PELARUTAN KARBIDA BAJA MANGAN AUSTENITIK - Bambang Widyanto; Achmad Sambas (Mesin, 2007)
Austenitic manganese steel is used for components which need good wear resistance and impact resistance. The application examples of austenitic manganese steel castings are in the mining industries such as rock crusher and dredge buckets, and in transportation industry, this material was used in railroad track work such as frog. However as-cast austenitic manganese steel is brittle with low toughness due to the presence of carbides. Hence, the as-cast austenitic manganese steel should be solution treated to dissolve the carbides into austenite phase, to improve its mechanical properties. Additionally, this research is enriched by using thickness parameter, to understand the influence of the dimension. The chemical composition in the casting process is in accordance with ASTM A 128 grade A. The solution treatment processes was done using a step heating procedure at temperature 575oC and 1050oC and determined heating time. Heating temperatures were determined based on Fe-Mn-C phase diagram and by the previous researches. Holding time was determined based on the literature, and heat transfer simulation result. The effects of the solution treatment were observed in the microstructure, grain size, and hardness of the specimens to obtain the optimal solution treatment that can be used. The objective of this research is to find the suitable heat treatment method in order to produce the desirable material properties and in this case, 160HB was obtained.